Strategi Dakwah Komunitas Sahabat Remaja Salihah dalam Menjaga Kehormatan Wanita Generasi Z di Kecamatan Medan Marelan - Anugrah, Indah; Sampurna, Ahmad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
This research discusses the Salihah Youth Friends Community in maintaining the honor of women towards generation Z. In line with the development of this era, teenagers are at risk of misguided behavioral tendencies. Through the Salihah Youth Friends Community, we can help teenagers in a better direction, such as those who previously did not cover their intimate parts are now covering their intimate parts, those who were still dating are now avoiding adultery, those who previously did not know much about Islam now know. The aim of this research was to determine the Strategy of the Salihah Youth Friends Community in maintaining the honor of Generation Z women. This research used a descriptive method with a qualitative approach. The data source in this research is direct information using interview, observation and documentation data collection techniques. The results of this research show that the da'wah strategy of the Salihah Youth Friends Community in maintaining the honor of generation Z women in Medan Marelan District is sending invitations to teenagers from nearby mosques to follow the agenda that will be implemented, da'wah through social media, sentimental strategies, rational strategies. With this strategy, teenagers in generation Z are more likely to have the right direction or path and can maintain their honor as Muslim women.